Pendampingan Belajar Anak yang Tinggal di Bawah Jembatan Landak dalam Menumbuhkan Motivasi Belajar di Gg. Semut Kelurahan Tanjung Hulu Kecamatan Pontianak Timur - Iwan Ramadhan; Jumardi Budiman; Nur Meily Adlika; Shilmy Purnama; Haris Firmansyah; Hadi Wiyono (Unika Santu Paulus Ruteng, 2022)
Various problems have occurred in implementing learning at home since the transition to online learning to prevent the Covid-19 outbreak. Parents at home are required to provide maximum guidance because parents as educators are tasked with guiding the child's learning process from a distance. However, not all parents can assist their children, so children experience obstacles and problems that require a role not only from parents. Not only that, children face several factors due to the lack of learning assistance, including the lack of student independence in learning caused by the unpreparedness of parents in assisting and guiding students to study at home and discomfort due to using gadgets. To check for a long time. The Tanjung Hulu District Government partners with the Tanjungpura University BEM. The method used in implementing this program is a classical approach carried out by providing learning materials that are easy and understandable for children. The results showed that the activities had run smoothly, starting with introductions, the provision of materials had been carried out well, and the children were also enthusiastic about participating in the implementation of this mentoring